Pengaruh Kualitas Pelayanan dan Harga Tiket terhadap Niat Beli Penumpang KA Jayabaya Kelas Ekonomi New Generation - Navisa, Novi; Priyanto, Sapto (EDUPEDIA Publisher, 2025)
In the era of rapid transportation and technology, people tend to choose efficient and economical means. PT KAI is adapting to meet these expectations, especially in improving the comfort of Economy class trains. Jayabaya train ticket prices, before becoming Jayabaya new Generation train, are the main driver of customer satisfaction. Price sensitive for consumers becomes a critical aspect in attracting customers. The addition of facilities on this train caused a tariff increase of Rp. 30.000,00. This study aims to analyze the effect of service quality and ticket prices on the interest in buying passengers Jayabaya new Generation Economy Class. This quantitative research uses the independent variables of service quality and ticket prices, as well as the dependent variable purchasing interest. Data were collected through questionnaires and secondary data from the number of passengers and ticket prices for Jayabaya new Generation economy class train. The method used is binary logistic regression. The results of data analysis using IBM SPSS Statistics 27 showed that the quality of Service (X1) does not partially affect the interest in buying passengers Jayabaya new Generation Economy Class (significance value 0.628 > 0.05). In contrast, the ticket price (X2) has a partial effect on the interest in buying Jayabaya economy class new Generation passengers significantly (significance value 0.003 < 0.05). Simultaneously, the quality of Service and ticket prices have a significant effect on buying interest (significance value 0.001).